“There is a Spy Living Next Door”: The Spy Reporting System and Everyday Life Under the Anticommunist Policy of the Park Chung-hee Government - 권혁은 (Korea journal, 2025)
Analyzing intelligence documents from the Yongsan Police Station in Seoul, this study examines how the spy-reporting system functioned in South Korea under the Park Chung-hee government and its impact on urban social relations. Drawing on 115 cases of spy reports from 1973 to 1977, this research reveals how anticommunist surveillance mechanisms penetrated everyday life and shaped urban communities. The study finds that the reporting system primarily targeted three groups: frequent movers in a rapidly urbanizing Seoul, individuals with connections to Japan or North Korea, and members of the urban lower class without stable employment, such as day laborers and bar workers. While previous research has focused on fabricated spy cases and democratization movements, this study uniquely illuminates how ordinary citizens internalized and practiced anticommunism in their daily lives. The findings suggest that anticommunist practices served as a means of managing social anxieties generated by rapid industrialization and urbanization, while simultaneously allowing urban residents to engage with state power. The spy-reporting system created communities based on exclusion rather than inclusion, as suspicious persons were systematically marginalized. This research contributes to our understanding of how state ideology shaped individuals’ everyday lives during South Korea’s developmental period and suggests that contemporary social issues partly stem from this historical legacy of surveillance and exclusion. KCI Citation Count: 0